2018
DOI: 10.3390/fishes3010015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fresh Azolla pinnata as a Low-Cost Supplemental Feed for Thai Silver Barb Barbonymus gonionotus

Abstract: Aquatic fern Azolla pinnata comprises significant high food value with a good proportion of protein, vitamins, and minerals. This study was carried out to examine the effect of fresh A. pinnata as a substitution of commercial fish feed (CFF) for Thai silver barb Barbonymus gonionotus. Post fingerlings of B. gonionotus were reared in five treatments, labeled T 1 to T 5 , by substituting 0%, 25%, 50%, 75%, and 100% protein of CFF with A. pinnata protein (dry matter basis) respectively for 56 days. The specific g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 20 publications
(17 reference statements)
5
37
0
5
Order By: Relevance
“…Conversely, Azolla and Lemna, which led to similar scores in our study, appear particularly well adapted for the partial substitution of fish feed. This is in agreement with previous studies showing the interest of those macrophytes as fish feed (Velásquez, 2016;Asimi et al, 2018;Das et al, 2018). Considering the limited impacts of macrophytes on water quality in our experimental pond conditions and commercial fish feed cost, the partial substitution of fish feed by macrophytes co-produced in situ would be a promising way to enhance sustainability of small scale fish farming.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, Azolla and Lemna, which led to similar scores in our study, appear particularly well adapted for the partial substitution of fish feed. This is in agreement with previous studies showing the interest of those macrophytes as fish feed (Velásquez, 2016;Asimi et al, 2018;Das et al, 2018). Considering the limited impacts of macrophytes on water quality in our experimental pond conditions and commercial fish feed cost, the partial substitution of fish feed by macrophytes co-produced in situ would be a promising way to enhance sustainability of small scale fish farming.…”
Section: Discussionsupporting
confidence: 92%
“…It has good palatability, high yield potential, and very large market demand [63,64]. Das et al [65] reported that, the highest average weight gain (AWG) and specific growth rate (SGR) were observed in fish fed at T1 (0% Azolla) compared to other treatments. However, the general growth and production performance of fish was higher in T2 (25% Azolla) and was gradually decreased with the increase in the levels of supplementary A. pinnata.…”
Section: Thai Silver Barb Barbonymus Gonionotusmentioning
confidence: 99%
“…4.4 **) Alanine 27.80 *) 5.4 **) Aspartic acid 8.77 *) 7.8 **) Glutamic acid 23.13 *) 9.6 **) Glycine 1.76 *) 4.3 **) Proline 0.01 *) 3.5 **) Serine 2.03 *) 4.1 **) Tyrosine 1.69 *) 3.1 **) Sources: Rusoff et al (1980), *) Morales (2018), **) Compeer and de Best (2018) Aquatic plants are one of the sources of vegetable protein which is widely used in fish farming especially of herbivorous fishes. The use of various aquatic plants such as giant salvinia (Salvinia molesta) (Mcintosh et al 2003;Bosire et al 2008), water lettuce (Pistia stratiotes) (Yudhitstira et al 2015), duckweed fern (Azolla pinnata) (Gangadhar et al 2015;Das et al 2018) and water hyacinth (Eichhornia crassipes) (Sotolu and Sule 2011;Mohapatra et al 2015;Hontiveros and Serrano 2015;) as a source of fish feed have been extensively studied. Duckweeds have a great potential to be developed in aquaculture industry.…”
Section: Discussionmentioning
confidence: 99%